Biomass-derived activated carbon material from native European deciduous trees as an inexpensive and sustainable energy material for supercapacitor application. (February 2021) - Jain, Amrita; Ghosh, Meena; Krajewski, Marcin; Kurungot, Sreekumar; Michalska, Monika
Highlights: Mixture of native European deciduous trees is used as raw material for supercapacitors. Activated carbon was synthesized by using pyrolysis followed by cavitation process. The carbon-based material in supercapacitor device offered a capacitance of 24 F g −1 with excellent durability for 10000 cycles. Abstract: Activated carbons are one of the possible electrode materials for supercapacitors (SCs), which are widely used in commercial applications. Herein, we reported the synthesis of a novel activated carbon derived through a cavitation process from the mixture of native European deciduous trees, Birch, Fagaceae, and Carpinus betulus (commonly known as European hornbeam), which was employed as the electrode material in SC. From the morphological and structural characterization, we observed that the prepared sample is a desirable carbon with good porosity and high specific surface area of about 614 m 2 g −1 . The electrochemical properties of the synthesized material were evaluated with a three-electrode configuration in 1.0 M H2 SO4 electrolyte. It was found that in device mode, the carbon material delivers a specific capacitance of 24 F g −1 at 0.25 A g −1 with excellent cycling stability of over 10000 consecutive charge/discharge cycles. Thus, our studies demonstrate the facile synthesis of biomass-derived carbon and its application as a versatile electrode material for SC applications. Graphical abstract: Image, graphical abstract